Elevating Artistic Value and Creativity Through Abstract Batik: Anomart and Pandono Batik As Educational Medium - Al Faruq, Moh. Yudik; Juni Amanullah; Muhammad Nasirul Umam (Universitas Negeri Semarang, 2024)
Anomart and Pandono Batik are hand-drawn batiks that combine abstract art with traditional batik techniques, creating unique pieces with high artistic value. The resulting abstract batik serves not only as a medium for artistic expression but also as an educational tool to enhance appreciation for art and culture. This study aims to: (1) Understand the artistic value and creativity conveyed through Abstract Batik by Anomart and Pandono as an educational medium for the community at Anomart and Pandono Batik SMEs in Laweyan, Surakarta. (2) Identify the forms of motifs created by the community through the learning model applied in Anomart and Pandono Batik education. The data sources include informants, locations and events, and documents. Data validity is ensured through source triangulation and informant reviews. The data analysis technique used is interactive analysis. Based on the research findings, it can be concluded: (1) The artistic value and creativity conveyed through Abstract Batik by Anomart and Pandono as an educational medium allow for the development of community artistic creativity, provide broader opportunities for artistic appreciation, and produce original works. This approach enables individuals to explore their ideas and emotions freely, creating room for innovation and unique personal interpretation. (2) The forms of motifs created by the community through the learning model applied in Anomart and Pandono Batik education in Laweyan, Surakarta, are hand-drawn batik. As a result, the patterns and motifs of Anomart and Pandono Batik are not bound by specific rules, tend to be abstract, and are consistently unique—this is the hallmark of Anomart and Pandono Batik.